Pemanfaatan Media PowerPoint Interaktif dalam Pembelajaran IPAS Materi Perkembangbiakan Tumbuhan di Sekolah Dasar - Andri Setyawan; Isabella Khoirina Reinata; Dias Tiara Putri Utomo (UNIB Press, 2023)
One of the interactive learning materials that elementary teachers can use is PowerPoint. This study aimed to determine the effectiveness of using PowerPoint interactive learning media in improving 4th grade primary school students’ knowledge of IPAS subjects, especially materials on plant varieties. This study used a pre-experimental research design with group pretest-posttest. The study was conducted during odd semesters of the 2023/2024 school year. The study sample included all 4th grade students, with up to 22 students sampled through a total sampling technique. The instruments used in this study were pretest and posttest questionnaires. The collected data were analyzed using descriptive statistics test, normality test, and paired sample t test. The results of statistical analysis showed that the mean value from pre-test (61.81) to post-test (84.09) increased by 37%. The paired sample t-test results show a statistically significant value of 0.000, so it can be concluded that there is a difference between before and after the intervention. Therefore, primary school teachers are encouraged to use learning media to improve students’ learning outcomes.